2011
DOI: 10.1111/j.1469-8137.2011.03780.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐regulated anion channels in the plasma membrane of Lilium longiflorum pollen protoplasts

Abstract: Summary• Currents through anion channels in the plasma membrane of Lilium longiflorum pollen grain protoplasts were studied under conditions of symmetrical anionic concentrations by means of patch-clamp whole-cell configuration.• With Cl ) -based intra-and extracellular solutions, three outward-rectifying anion conductances, I Cl1 , I Cl2 and I Cl3 , were identified. These three activities were discriminated by differential rundown behaviour and sensitivity to 5-nitro-2-(phenylpropylamino)-benzoate (NPPB), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 63 publications
(152 reference statements)
3
30
0
Order By: Relevance
“…Similar to patch-clamp analysis of anion currents in lily pollen tube protoplasts (Tavares et al, 2011a), our analysis revealed depolarization-activated, slowly deactivating currents in wild-type Columbia-0 (Col-0), whereas typical S-type anion currents were absent or strongly reduced in slah3-1, slah3-2, and cpk2-1 cpk20-2 mutant cells ( Figure 7B). A plot of the steady state currents from membrane voltages clamped from 2200 mV to +80 mV (D = 20 mV) revealed significantly reduced anion currents in slah3-1-, slah3-2, and cpk2-1 cpk20-2 pollen tubes in both chloride-based (see Supplemental Figure 12 online) and nitratebased solution, pointing to a function for CPK2 and CPK20 in S-type anion channel regulation ( Figure 7C).…”
Section: Cpk2/cpk20-mediated Activation Of Slah3 Currents In X Laevisupporting
confidence: 49%
See 3 more Smart Citations
“…Similar to patch-clamp analysis of anion currents in lily pollen tube protoplasts (Tavares et al, 2011a), our analysis revealed depolarization-activated, slowly deactivating currents in wild-type Columbia-0 (Col-0), whereas typical S-type anion currents were absent or strongly reduced in slah3-1, slah3-2, and cpk2-1 cpk20-2 mutant cells ( Figure 7B). A plot of the steady state currents from membrane voltages clamped from 2200 mV to +80 mV (D = 20 mV) revealed significantly reduced anion currents in slah3-1-, slah3-2, and cpk2-1 cpk20-2 pollen tubes in both chloride-based (see Supplemental Figure 12 online) and nitratebased solution, pointing to a function for CPK2 and CPK20 in S-type anion channel regulation ( Figure 7C).…”
Section: Cpk2/cpk20-mediated Activation Of Slah3 Currents In X Laevisupporting
confidence: 49%
“…This cytosolic anion gradient matched the plasma membrane anion fluxes, as described by Zonia et al (2002), and currents, as described by Tavares et al (2011a). The cytosolic gradient was characterized by high chloride concentration in a cytosolic domain ranging from ;20 to ;40 µm behind the tip.…”
Section: Correlation Between Anion and Ca 2+ Homeostasismentioning
confidence: 99%
See 2 more Smart Citations
“…In guard cells, Ca 2+ signals can be transduced from some CDPKs or other Ca 2+ sensor proteins to various types of ion channels, such as K + in channels, nonselective Ca 2+ -permeable channels, and S-type anion channels, to regulate stomatal movements (Schroeder and Hagiwara, 1989;Li et al, 1998;Berkowitz et al, 2000;Mori et al, 2006;Geiger et al, 2010;Zou et al, 2010). Recently, Cl 2 channels and outward K + channels were reported to be regulated by intracellular Ca 2+ in pollen tubes (Tavares et al, 2011;Wu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%